Does Large-Scale Infrastructure Investment Alleviate Poverty? Impacts of Rwanda's Electricity Access Roll-Out Program. (January 2017) - Lenz, Luciane; Munyehirwe, Anicet; Peters, Jörg; Sievert, Maximiliane
Highlights: We study impacts of grid electrification on households, SMEs, health centers and schools. We find only weak impacts on classical poverty indicators. The median electricity consumption of households is very low at 6 kWh per month. Productive take-up is low among households and heterogeneous among enterprise types. We call for cost–benefit comparisons between on-grid and off-grid energy solutions. Summary: The objective of the United Nations Sustainable Energy for All initiative (SE4All) is to provide electricity by 2030 to the 1.1 billion people in developing countries that hitherto lack access. The OECD/IEA quantifies the investment requirements of this to be at 640 billion USD. Little evidence exists on socio-economic impacts of electrification. The present paper is the first to causally investigate the effects of electrification in Africa on all beneficiary groups. The electrification program under research, the Rwandan Electricity Access Role-Out Program (EARP), is one of the largest in the world. Our analysis is based on a panel of 974 households, a full-census survey among health centers, and qualitative surveys among 83 micro-enterprises and 50 schools. We find that EARP has been remarkably effective in increasing the connection numbers among all beneficiary types. Around 3.5 years after electrification, the quantity of consumed electricity and the uptake of appliances, though, remain low. Noteworthy impacts are decreasing energy expenditures and a considerable reduction in dry-cell battery consumption with potential environmental benefits. Beyond this, electricity mostly facilitates people's life, but there is only weak evidence for impacts on classical poverty indicators such as income, health, and education. We conclude by calling for more research on the comparison of on-grid and off-grid electrification with respect to impact potentials, costs, and people's willingness to pay in order to inform the way forward within the SE4All endeavor.